The Influence of Good Corporate Governance and Company Size on Financial Performance (Study on Property and Real Estate Company Listed in Indonesia Stock Exchange for the Period 2014-2016) - B1034141007, Ilmira Rosalin (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
This study aims to examine the influence of good corporate governance (GCG) and company size on the financial performance of property and real estate companies. The indicators of GCG used are the size of board of director and the size of board of commissioner. Financial performance as a dependent variable is measured by ROA. The data used is secondary data obtained from the financial and annual report through the website of Indonesia Stock Exchange (IDX). The population of this research is property and real estate sector companies listed on IDX for the period 2014-2016. Total sample used are 35 companies that is selected by purposive sampling technique. The data of this study is analyzed with multiple linear regression analysis. The results of this study indicates that the variable of GCG indicators and company size simultaneously have a significant influence on financial performance. In partial, the size of board of commissioner significantly has a positive influence on financial performance. Meanwhile, the size of board of director and company size partially have no significant influence on financial performance. Keywords: Good Corporate Governance, Board of Director, Board of Commissioner, Company Size and Financial Performance.Adestian, Y. (2015). Pengaruh Dewan Komisaris, Dewan Direksi, Dewan Komisaris Independen, Komite Audit dan Ukuran Perusahaan pada Kinerja Perusahaan Perbankan yang Listing di BEI Tahun 2012-2014. http://eprints.dinus.ac.id/id/eprint/17262.Ahmed, E., & Hamdan, A. (2015). The Impact of Corporate Governance on Firm Performance: Evidence From Bahrain Stock Exchange. European Journal of Business and Innovation Research, Vol.3, No.5, pp. 25-48.Arifin. (2005). Peran Akuntan dalam Menegakkan Prinsip Good Corporate Governance pada Perusahaan di Indonesia (Tinjauan Perspektif Teori Keagenan). Sidang Senat Guru Besar, Semarang: Universitas Diponegoro.Bodroastuti, T., Tirtono, T., & Setiawan, T. T. (2015). Pengaruh Struktur Corporate Governance terhadap Kinerja Keuangan (Studi Empiris pada Perusahaan Perbankan BUMD Jawa Tengah). Management Dynamics Conference. Semarang: Universitas Negeri Semarang.Bukhori, I. (2012). Pengaruh Good Corporate Governance dan Ukuran Perusahaan terhadap Kinerja Perusahaan (Studi Empiris pada Perusahaan yang Terdaftar di BEI 2010). Semarang : Universitas Diponegoro.Creswell, J. W. (2009). Research Design Pendekatan Penelitian Kualitatif, Kuantitafi and Mixed. Yogyakarta: Pustaka Pelajar. Penerjemah Achmad Fawaid.Daniri, M. A. (2014). Lead by GCG. Jakarta: Gagas Bisnis Indonesia.Doğan, M. (2013). Does Firm Size Affect The Firm Profitability? Evidence from Turkey. Research Journal of Finance and Accounting, Vol.4, No.4, pp. 53-59.Haniffa, R., & Hudaib, M. (2006). Corporate Governance Structure and Performance of Malaysian Listed Companies. Journal of Business Finance & Accounting, 33(7) & (8), September/October 2006, pp. 1034-1062.Hidayat, R. (2015). Pengaruh Good Corporate Governance dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di BEI 2010-2013). Jom FEKON Vol. 2 No. 1,https://jom.unri.ac.id/index.php/JOMFEKON/article/view/9787.Jónsson, B. (2017). Does the size matter? The relationship between size and profitability of Icelandic firms. BIFRÖST JOURNAL OF SOCIAL SCIENCE, pp. 43-55.KNKG. (2006). Pedoman Umum Corporate Governance Indonesia. www.ecgi.org/codes/documents/indonesia_cg_2006_id.pdf.Kusumawardhani, I. (2012). Pengaruh Corporate Governance, Struktur Kepemilikan dan Ukuran Perusahaan terhadap Manajemen Laba. Jurnal Akuntansi dan Sistem Teknologi Informasi, Vol. 9, No.1, Oktober 2012, 41-54.Mulyati, S. M. (2011). Pengaruh Penerapan Good Corporate Governance terhadap Kinerja Keuangan Perusahaan (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2007-2009). Skripsi, Semarang: Universitas Negeri Semarang.OECD. (2004). OECD Principles of Corporate Governance. http://www.oecd.org/corporate/ca/corporategovernanceprinciples/31557724.pdf.Pervan, M., & Višić, J. (2012). Influence of Firm Size on Its Business Success. Croatian Operational Research Review (CRORR), Vol. 3, 213-223.Raymond, A. (2014). Pengaruh Komposisi Struktur Dewan Perusahaan terhadap Kinerja Keuangan Perusahaan Operator Seluler di Indonesia. Journal Ilmu Manajemen, Vol 4,http://jurnal.um-palembang.ac.id/ilmu_manajemen/article/view/251/223.Santoso, S. (2012). Aplikasi SPSS pada Statistik Parametrik. Jakarta: PT. Elex Media Komptindo.Susanti, A. (2016). Pengaruh Asimetri Informasi, Ukuran Perusahaan, Kepemilikan Manajerial, dan Capital Adequacy Ratio terhadap Manajemen Laba (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2011-2013). JOM (Fekon), Vol. 3, No. 1, (Februari 2016).Tisna, G. A., & Agustami, S. (2016). Pengaruh Good Corporate Governance dan Ukuran Perusahaan terhadap Kinerja Keuangan Perusahaan (Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2010-2014). Jurnal Riset Akuntansi dan Keuangan, Vol. 4, No.2, p. 1035-1046 , http://ejournal.upi.edu/index.php/JRAK/article/view/4038.Wati, L. M. (2012). Pengaruh Praktek Good Corporate Governance terhadap Kinerja Kinerja Keuangan Perusahaan di Bursa Efek Indonesia. Jurnal Manajemen, Vol 1, No 1, September 2012.Widyati, M. F. (2013). Pengaruh Dewan Direksi, Komisaris Independen, Komite Audit, Kepemilikan Manajerial dan Kepemilikan Indtitusional terhadap Kinerja Keuangan. Jurnal Ilmu Manajemen, Vol. 1, No. 1, p. 234-249 , jurnalmahasiswa.unesa.ac.id/index.php/jim/article/view/1509.www.idx.co.idwww.sahamok.comYasser, Q. R., Entebang, H., & Mansor, S. A. (2011). Corporate Governance and Firm Performance in Pakistan: The Case of Karachi Stock Exchange (KSE)-30. Journal of Economics and International Finance Vol. 3(8), pp. 482-491.